Almanya'da Aleviler: Frankfurt, Darmstadt, Wuppertal, Troisdorf, Mannheim, Bergkamen, Köln bölgelerinde yü- rütülen Alan Araştırması Raporu - Menemencioğlu Temren, Belkıs (Alevilik–Bektaşilik Araştırmaları Dergisi, 2011)
The goal of the field study conducted by Prof. Dr. Belkıs Menemencioğlu (Temren) as a project of the Alevi-Bektashi Cultural Institute in the cities Frankfurt, Darmstadt, Wuppertal, Troisdorf, Mannheim, Bergkamen and Köln was to draw an ethnographic sketch of the Alevis living in Germany in order to identify the basic outlines of their daily difficulties where they exist. As a preliminary work it serves as a basis and directory for further research on a larger scale, necessary for harmonious and peaceful existence for the Alevis in the culture they live in preserving their own cultural characteristics. Following subjects were detected: Their coming to Germany, their adaptation phase and evaluation of their life here, inquiry of the definition of their social identity, inquiry of access to information and their suggestions, inquiry if they can live the Alevi culture as they please, their expectations, detection of their estimation regarding main institutions and concepts of Alevism, detection of attitudes towards the alliance and restructuring of Alevism and Bektashism, attitudes towards Alevism and Islam and the differentiation/convergency of Alevism and Sunnism.
Keywords: anahtar kelime